TRENDS IN SEDENTARY BEHAVIOR AMONG THE SOUTH BRAZILIAN STUDENTS (Fiep Bulletin - online, 2023)
Introduction: Sedentary behavior has been a matter of concern for researchers around the world, especially in Brazil. Objective: This study compared the moderate–vigorous physical activity and sedentary behavior between the years of two surveys (2008 and 2017), relating these behaviors to waist circumference. Methods: Cross sectional study, included 1783 students, both sexes, aged 10 to 17 years were considered:  2008 (n = 977) and 2017 (n = 806). The studies were carried out in public schools in the municipality of southern Brazil. The level of physical activity was assessed through an energy expenditure questionnaire. The waist circumference was considered high ≥75th percentile for age and sex. The students were grouped according to the levels of moderate–vigorous physical activity. Sitting time was used as a proxy of sedentary behavior. Results: The proportion of active boys in 2008 (62.2%) was higher than in 2017 (34.1%; p
Keywords: Sedentary behaviors; Waist circumference; Anthropometry; Adolescents; Physical activity